Production diversification and commercialization of family farmers settled of mirandopolis (sp): Contributions of the food acquisition program - da Silva Modenese, Valeria [UNESP]; Sant'Ana, Antonio Lazaro [UNESP] (FapUNIFESP (SciELO), 2019)
The Food Acquisition Program (PAA) aims to ensure food in quantity and quality for people in food insecurity situation, as well as to encourage the production and commercialization of the products from family farms. In this paper, the effects of the PAA were analyzed in relation to crop production, commercialization and income of the settled family farmers who participated in this program, in the Purchase for Simultaneous Donation modality, in Mirandopolis (SP), based on the view of these farmers. The methodology was based on the application of questionnaires to 50 beneficiaries of the PAA, in 2014, residing in three settlements in that municipality. Among the multidimensional effects of the PAA, the expansion of production diversity for commercialization purposes; the reduction of the participation in other commercialization channels, mainly through intermediaries, and the significant increase in income, especially from the most economically vulnerable families, were evident.
Diversificação produtiva e de comercialização de agricultores familiares assentados de mirandópolis (sp): Contribuições do programa de aquisição de alimentos
Keywords: Family farming; Government purchases; PAA; Public policy